Customer Satisfaction and Profitability in Traditional vs. Digital Banking: A Comparative Study (International Journal of Food and Nutritional Sciences, 2022)
This study examines the comparative profitability of traditional versus digital banking models from the perspective of customer satisfaction and expectations. As the financial sector evolves, understanding how customer satisfaction impacts profitability is crucial for both traditional banks, known for their personalized service, and digital banks, which offer convenience and technological innovation. The research highlights that customer satisfaction is a significant driver of profitability in both banking models. Traditional banks benefit from strong customer loyalty and long-term relationships, despite higher operational costs. Digital banks, with their lower operational expenses and advanced technological features, attract a tech-savvy customer base, potentially leading to higher profit margins. The findings suggest that banks must balance operational efficiency with evolving customer preferences to enhance profitability. Recommendations include integrating digital solutions for traditional banks and continuing innovation and security enhancements for digital banks. This study provides valuable insights for banking institutions aiming to navigate the dynamic financial landscape and optimize their profitability through improved customer satisfaction.